2017
DOI: 10.1177/1359105317705982
|View full text |Cite
|
Sign up to set email alerts
|

Enduring somatic threat perceptions and post-traumatic stress disorder symptoms in survivors of cardiac events

Abstract: PTSD due to acute cardiovascular events may be uniquely defined by enduring perceptions of somatic threat. We tested whether PTSD at 1 month post-acute coronary syndrome (ACS) indeed required both high peritraumatic threat during the ACS and ongoing cardiac threat perceptions. We assessed peritraumatic threat during emergency department (ED) enrollment of 284 patients with a provisional ACS diagnosis, and cardiac threat perceptions and PTSD symptoms 1 month post-discharge. In a multiple regression model with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 47 publications
0
29
0
Order By: Relevance
“…Traditional PTSD screening instruments or clinical interviews, such as the PDS and CAPS used in our study, are keyed to a single medical event in the past (i.e., the diagnosis and acute care/intervention for ACS), but they do not capture present and future-oriented re-experiencing symptoms of PTSD due to enduring threats of recurrence and functional decline in the wake of ACS; likewise avoidance and hyperarousal symptoms may also present in a different manner and with different psychological consequences [37]. A recent study confirmed the clinical importance of enduring somatic threat for PTSS in patients with ACS showing that a high level of acute distress at hospital admission was only predictive of ACS-induced PTSS 1 month later in those patients who also perceived ongoing cardiac threat in the form of anxious thoughts and feelings about cardiac symptoms [38]. A research agenda has been proposed to develop a taxonomy to recategorize the gamut of distressing psychological symptoms prevalent in survivors of a medical disease beyond the levels of PTSD and other psychiatric disorders [35].…”
Section: Discussionmentioning
confidence: 76%
“…Traditional PTSD screening instruments or clinical interviews, such as the PDS and CAPS used in our study, are keyed to a single medical event in the past (i.e., the diagnosis and acute care/intervention for ACS), but they do not capture present and future-oriented re-experiencing symptoms of PTSD due to enduring threats of recurrence and functional decline in the wake of ACS; likewise avoidance and hyperarousal symptoms may also present in a different manner and with different psychological consequences [37]. A recent study confirmed the clinical importance of enduring somatic threat for PTSS in patients with ACS showing that a high level of acute distress at hospital admission was only predictive of ACS-induced PTSS 1 month later in those patients who also perceived ongoing cardiac threat in the form of anxious thoughts and feelings about cardiac symptoms [38]. A research agenda has been proposed to develop a taxonomy to recategorize the gamut of distressing psychological symptoms prevalent in survivors of a medical disease beyond the levels of PTSD and other psychiatric disorders [35].…”
Section: Discussionmentioning
confidence: 76%
“…26,27 It may be possible that the development of anxiety or "post-traumatic" stress response described in patients after life threatening events like ACS may also affect predisposed individuals after cardiac evaluation. 28 In any case, there is strong evidence showing that low risk or non-cardiac chest pain associated with anxiety and other psychological comorbidities are associated with more frequent medical visits than community norms. 25,29 It appears that normal test results and reassurance are not enough to allay the residual anxiety and persistent belief in a cardiac cause of their chest pain symptoms.…”
Section: Accepted Manuscript 11mentioning
confidence: 99%
“…Further research is required to test whether the association between perceived threat in the ED and PTSD symptoms at 30 days among patients with nontraumatic medical emergencies is mediated by peritraumatic dissociation. In addition, prior research in patients with acute coronary syndrome suggests that perceived threat in the ED predicts PTSD symptoms at 30 days primarily in patients who continue to report ongoing body‐focused worry in the month after discharge, so future research should assess enduring somatic threat perceptions in these patients …”
Section: Discussionmentioning
confidence: 99%
“…In addition, prior research in patients with acute coronary syndrome suggests that perceived threat in the ED predicts PTSD symptoms at 30 days primarily in patients who continue to report ongoing body-focused worry in the month after discharge, so future research should assess enduring somatic threat perceptions in these patients. 37 There are currently large ongoing studies evaluating PTSD among traumatic injury survivors (AURORA study, https://www.med.unc.edu/itr/aurora-study) as well as patients with acute stroke, acute coronary syndrome, and post-cardiac arrest syndrome (REactions to Acute Care and Hospitalization [REACH] study, NCT03605693). 27 Our results expand upon the REACH study as it identifies an additional cohort of subjects who are also at risk for a high degree of perceived threat in the ED and the subsequent development of PTSD symptoms.…”
Section: Discussionmentioning
confidence: 99%